PERTANGGUNGJAWABAN HUKUM RUMAH SAKIT, KORPORASI DAN DOKTER TERHADAP MALPRAKTEK YANGDILAKUKAN OLEH DOKTER (Tinjauan Yuridis Atas Putusan Pengadilan Negeri Jakarta Selatan No. 312/Pdt.G/2014/PN.Jkt.Se. Jo. Putusan Pengadilan Tinggi DKI jakarta No. 240/Pdt/2016/PT.DKI. Jo. Putusan Mahkamah Agung RI No. 3695 K/Pdt/2016) - Ambari (2022)
In every health service activity in the hospital often poses medical risks that can cause patient losses. Against these medical risks, it will always demand legal liability for doctors, hospitals and corporations civilly. In the case between Martini Nazif patients and Asri Hospital as a Decision of the South Jakarta District Court No. 312/Pdt.G/2014/PN. Jkt.Se. Jo. Decision of the DKI Jakarta High Court No. 240/Pdt/2016/PT. DKI. Jo. Decision of the Supreme Court of the Republic of Indonesia. No. 3695 K/Rev/2016, is an example of the legal liability of doctors, hospitals and corporations to provide material and immaterial damages in a mutually beneficial manner to patients for medical negligence committed by doctors, thereby causing harm to patients in the form of the death of the patient's first child. Legal liability for doctors is clearly stated in article 1365 of the Criminal Code, while legal liability for hospitals and corporations as health service facilities and owners of health facilities is explained in article 1367 of the Criminal Code and Article 52 PP No. 47 of 2021 concerning the Implementation of the Hospitalization Sector.